THE USING OF WHATSAPP IN TEACHING PRONUNCIATION PRACTICE TO THE THIRD SEMESTER STUDENTS OF TADRIS ENGLISH STUDY PROGRAM IN IAIN PALU - afifah afifah (Datokarama English Education Journal, 2021)
This research focuses on the using of WhatsApp in teaching pronunciation practice to the third semester students of Tadris English Study Program in IAIN Palu. The research question is “How is the using of WhatsApp in teaching Pronunciation Practice to the third semester students of Tadris English Study Program in IAIN Palu?” This is a qualitative research by using two instruments of data collections namely questionnaire and interview. The participants consisted of 19 third semester students of Tadris English Study Program of State Institute for Islamic Studies (IAIN) Palu. The researcher conducted five meetings of Pronunciation Practice class to the participants via WhatsApp before distributing the questionnaire and interview sheet. The questionnaire consisted of five questions by applying Likert Scale, while the interview consisted of ten questions. From the questionnaire and interview, the researcher concludes that the using of WhatsApp in teaching Pronunciation Practice to the third semester students of Tadris English Study Program in IAIN Palu is practical. The students could understand the material shared via WhatsApp in the form of documents shared, videos shared, as well as voice recording shared. They could use the features in WhatsApp well such as sharing documents, voice notes, sharing videos, video call and so on in learning pronunciation practice. The students like Pronunciation Practice Class and enjoy studying it via WhatsApp. Learning Pronunciation Practice via WhatsApp has some advantages such as time flexibility as well as structured and easily accessed materials. However, it also has some limitations such as internet data availability and video call limitation. Besides, the participants faced several obstacles in learning Pronunication Practice via WhatsApp, such as the limitation of smartphone memory to save files, down internet server, and unavailability of internet data. Nevertheless, they could passed those obstacles well by deleting some unused files to give more space to the memory and finding out wifi connection to stay connected to WhatsApp when the server was down or they ran out of internet data. They could understand the teaching of Pronunciation Practice via WhatsApp by downloading and reading the documents shared, the videos shared, and the voice recording shared by the lecturer. When they found a difficulty, they asked their friends or the lecturer via WhatsApp group.